PENGARUH KEPUASAN KONSUMEN, KUALITAS PRODUK, CITRA MEREK, DAN WORD OF MOUTH TERHADAP MINAT BELI ULANG - Isnanda Zainur Rohman (MANAJEMEN DEWANTARA, 2022)
The purpose of this study is to understand how consumer satisfaction, product quality, brand image, and word of mouth affect repurchase interest at Chatime in Yogyakarta. The data for this study was gathered using a questionnaire distributed via Google Form to 200 respondents using the purposive sampling method. The criteria of the respondents is they had purchased Chatime products within the last three months. Based on the findings of this study, the following conclusions were reached: (1) Consumer satisfaction has a positive and significant effect on repurchase interest with a t-value 3.224 and a significance value 0.001; (2) Product quality has an effect significant on repurchase interest with a t-value 1.696 and a significance value of 0.001; (3) Brand image has a significant on repurchase intention with a t-value 1.527 and a significance value 0.028; and (4) Word of mouth has a positive and significant effect on repurchase interest with a t-value 6.596 and a significance value of 0.000.